CU06-1004 as a promising strategy to improve anti-cancer drug efficacy by preventing vascular leaky syndrome - Park, Songyi; Lee, Sunghye; Kim, Dongyeop; Kim, Hyejeong; Kwon, Young-Guen (Frontiers in Pharmacology, 2023)
Background: Interleukin-2 (IL-2) is the first cancer therapeutic agent with an immunomodulatory function. Although it has been experimentally proven to be effective against metastatic renal cell carcinoma and metastatic melanoma, the clinical application of high-dose IL-2 (HDIL-2) has been limited because of its short half-life and severe side effects, such as vascular leakage syndrome (VLS) or capillary leaky syndrome (CLS). However, methods for overcoming this issue have not yet been identified. Methods: We discovered CU06-1004, an endothelial dysfunction blocker, through a previous study, and co-treated with IL-2 immunotherapy to confirm its inhibitory effect on HDIL-2-induced endothelial permeability. CU06-1004 was co-administered with HDIL-2 for four days in an in vivo mouse model. After the drug injection, the mice were sacrificed, and Evans blue staining was performed. Results: In vitro, HDIL-2 treatment decreased HUVEC stability, which was rescued by co-treatment with CU06-1004. In our mouse model, co-administration of CU06-1004 and HDIL-2 prevented HDIL-2-induced vascular leakage by normalizing endothelial cells. Notably, the HDIL-2 and CU06-1004 combination therapy considerably reduced tumor growth in the B16F10 melanoma mouse model. Conclusion: Our data suggest that CU06-1004 acts as a potential anticancer drug candidate, not only by preventing HDIL-2-induced VLS but also by enhancing the anticancer effects of HDIL-2 immunotherapy.